2019
DOI: 10.1038/s41467-019-08389-6
|View full text |Cite
|
Sign up to set email alerts
|

Binder-free graphene oxide doughs

Abstract: Graphene oxide (GO) sheets have been used to construct various bulk forms of GO and graphene-based materials through solution-based processing techniques. Here, we report a highly cohesive dough state of GO with tens of weight percent loading in water without binder-like additives. The dough state can be diluted to obtain gels or dispersions, and dried to yield hard solids. It can be kneaded without leaving stains, readily reshaped, connected, and further processed to make bulk GO and graphene materials of arb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 50 publications
4
48
0
Order By: Relevance
“…Like bulk materials, 2D films can achieve high toughness via the mechanism of crack arrest or plastic deformation (5). Recently, inspired by the hierarchical microscale/nanoscale structure and abundant interface interactions of natural nacre (6), various interfacial interactions, such as hydrogen bonding, ionic bonding, π-π stacking interactions, and covalent bonding, have been demonstrated to enhance the toughness of graphene-based films (7)(8)(9)(10). These interfacial effects can not only inhibit the crack propagation of graphene films but also effectively improve their plastic deformation.…”
mentioning
confidence: 99%
“…Like bulk materials, 2D films can achieve high toughness via the mechanism of crack arrest or plastic deformation (5). Recently, inspired by the hierarchical microscale/nanoscale structure and abundant interface interactions of natural nacre (6), various interfacial interactions, such as hydrogen bonding, ionic bonding, π-π stacking interactions, and covalent bonding, have been demonstrated to enhance the toughness of graphene-based films (7)(8)(9)(10). These interfacial effects can not only inhibit the crack propagation of graphene films but also effectively improve their plastic deformation.…”
mentioning
confidence: 99%
“…Previous studies have shown that GO and carbon nanotubes' dispersions of different concentrations can be divided into four states. [29,52] In our experiment, increasing GO/G concentrations results in a continuous transition between four states, from a dilute dispersion (<10 mg mL −1 ) to a thick paste (10-50 mg mL −1 ), a free-standing gel (50-100 mg mL −1 ), and eventually, a kneadable, playdough-like material (>100 mg mL −1 ). These four states were further transformed into 1D graphene fibers, 2D graphene films, or 3D graphene doughs using various material-processing techniques ( Figure S25, Supporting Information).…”
Section: The Four States Of Go/gmentioning
confidence: 80%
“…Preparation of a Continuous Transition between Four States: The preparation method was modified from a published article. [29] The preparation method of the diluted dispersion is mentioned above. The thick paste was prepared using high-pressure homogenizers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations